Façade Optimization Through BIM Technology Based on LEED Assessment of Existing Building Energy - Salo, Deya Aldeen Saleh Ali (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
Building sustainability in architecture has become a significant concern, especially for building energy since it is one of the most important aspects to be considered. In architecture, the sustainable building includes different areas such as daylight, airflow, ventilation, solar performance, etc. These areas have different effects regarding building sustainability, energy consumption, and human comfort, which have been considered recently. Daylight is the primary natural source that affects the building energy in terms of visual comfort. This lets the architects pay attention to the need for daylight consideration. Building façade is one of the most important considerations to enhance the daylight performance since it introduces the sunlight to the building interior. Regarding this, the research aims to test a method to enhance the building daylight performance regarding visual comfort by optimizing an existing building façade based on LEED criteria through BIM technology. In order to achieve that, the research explained the important data of daylight parallel to LEED daylight criteria in an office building in Jordan, which is in the climate zone of the middle east. In addition, the research focused on the BIM technology in different manners to help the architects connect all building drawing, data, and energy performance linked to each other to test and accurately produce different solutions. Keywords: Façade Technology, BIM, Building Daylight, LEED Assessment, Façade Optimization

ÖZ: Mimaride yapı sürdürülebilirliği, özellikle bina enerjisi söz konusu olduğunda dikkate alınması gereken en önemli unsurlardan biridir. Mimaride sürdürülebilir yapı; Gün ışığı, binadaki havalandırma ve hava akışı, güneş enerjisi vb. gibi farklı alanları içerir. Bina üzerinde birçok etkisi olan, enerji tüketimi ve insan konforu son zamanlarda ele alınan başlıca etkilerdir. Gün ışığı, bina enerjisini farklı dönemlerde etkileyen birincil doğal kaynaktır ve bu da mimarların gün ışığı ihtiyacını mimari tasarımlarda dikkate almalarında büyük önem taşır. Bina cephesi, gün ışığı performansını arttırmak için, ışığın bina içerisine alınmasında en önemli unsurlardan biridir. Bununla ilgili olarak yapılan bu araştırmada, mevcut bir bina cephesi incelenip, BIM teknolojisi ile LEED kriterlerine göre optimize edilerek, görsel konfor açısından bina günışığı performansını artırmak amaçlanmaktadır. Bunu elde edebilmek için yapılan araştırmada, LEED gün ışığı kriterlerine paralel olarak, Ortadoğu ikliminde bulunan Ürdün’de bir ofis binasının cephesi incelenerek, gün ışığı verileri doğrultusunda bu bina cephesi üzerinde çalışma yapılmıştır. Bu bağlamda yapılan araştırmada, mimarların farklı çözümleri doğru bir şekilde test etmek ve üretmek için tüm mimari bina çizimlerini, buna bağlı verileri ve bina enerji performansını birbirine bağlamalarına yardımcı olmak için farklı yaklaşımlarla BIM teknolojisine odaklanıldı. Anahtar Kelimeler: Cephe Teknolojisi, BIM, Bina Gün Işığı, LEED Değerlendirmesi, Cephe Optimizasyonu
Master of Science in Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2022. Supervisor: Prof. Dr. Sadiye Müjdem Vural.
Keywords: Architecture; Dayligh--Architectural Design--Facade Elements--Facades; Smart Lighting--Design and Architecture; Lighting, Architectural; Sustainable Buildings--Energy Consrvation--Energy Consumption; Façade Technology; BIM; Building Daylight; LEED Assessment; Façade Optimization